Media Influencephoto Story On The Ability To Write Procedure Texts Of Grade VII At Mts NW Pringgasela - Neni Suryanirmala; Zul Haeri (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The purpose of this study is to describe the influence of the use of photo story in learning to write procedural texts for class VII MTS NW Pringgasela. This study evaluates the influence of the use of mediaphoto story in learning to write procedural texts in the experimental class compared to the control class. The results of the study showed that the average score of students in the experimental class (82.67) was significantly higher than that of the control class (72.67). The paired t-test showed a very significant difference between the pretest and posttest scores in both classes, with a significance value (sig) of less than 0.05. This indicates that the use of mediaphoto story has a significant positive impact on improving students' procedural text writing skills. The implications of this study underscore the effectiveness of the media photo story as a learning tool that can motivate students and improve their understanding of writing procedural texts